Critical bloodstream infection caused by Chromobacterium violaceum: a case report in a 15-year-old male with sepsis-induced cardiogenic shock and purpura fulminans - Wang, Xueqing; Tu, Yunliang; Chen, Yingqun; Yang, Huilin; Luo, Minghua; Li, Yanyan; Huang, Lei; Luo, Hua (Frontiers in Medicine, 2024)
Chromobacterium violaceum (C. violaceum) is a gram-negative bacillus that is widespread in tropical and subtropical areas. Although C. violaceum rarely infects humans, it can cause critical illness with a mortality rate above 50%. Here, we report the successful treatment of a 15-year-old male who presented with bloodstream infection of C. violaceum along with sepsis, specific skin lesions, and liver abscesses. Cardiogenic shock induced by sepsis was reversed by venoarterial extracorporeal membrane oxygenation (VA ECMO). Moreover, C. violaceum-related purpura fulminans, which is reported herein for the first time, was ameliorated after treatment. This case report demonstrates the virulence of C. violaceum with the aim of raising clinical awareness of this disease.